IMPROVING READING COMPREHENSION THROUGH USING OF THE HERRINGBONE TECHNIQUE IN TEACHING READING - Hasanah, Syarifatul; Ni'mah, Mamluatun; Kholili, Achmad (Nurul Jadid University, 2023)
This study investigated the effectiveness of the Herringbone technique in improving reading comprehension skills among class XI students. The research followed a quasi-experimental design, with an experimental group receiving instruction using the Herringbone technique and a control group receiving traditional instruction. Pre-test and post-test assessments were conducted to measure the participants' reading comprehension abilities. The results indicated a significant improvement in the reading comprehension scores of the experimental group compared to the control group. These findings suggest that the Herringbone technique is more effective than traditional methods in enhancing reading comprehension skills. The implications of this study emphasize the importance of incorporating interactive and collaborative instructional approaches in English language teaching to foster critical thinking and deeper understanding of texts. Future research should explore the long-term effects and applicability of the Herringbone technique in diverse educational contexts. Overall, the Herringbone technique shows promise as an effective approach to enhance reading comprehension instruction and support language development among students.